Denitrification of Activated Sludge in The Presence of Different Organic Substrates - Agustiani, Dwi; Yamagishi, Takao (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2004)
The efect organic carbon on denitrifying activity was studied in batch reactor. For reactors were operated in paralel under anoxic condition in four different donor electrons. which were acetic acid (Reactor A) , methnol (Reactor M), phenol (Reactor P), and glucose (Reactor G) . The reactors. were fed with the artificial waste, which contain 721.8 mg/ NaNO3 The concentration or organic carbon added to the reactors were varied from TOD: N ratio of 0.5:1; 1:1, 1.5 : 1, to 2:1. The denitrification activity was e timated by measuring the reduction rate of nitrogenous oxide and N2O gas production. The denitrification capacity of adapted-sludge was also investigated, and the rates were estimated from the cumulative N2O (without acetylene inhibition) and N2 gas production . Reduction rate of nitrogenous oxide in all reactors increused during the investigation; the increase reduction rate were correlated to the increase of organic carbon concentration. The maximum reduction rate of nitrogenous oxide in reactor A was higher than those of the others. However, reduction rate in reactor M was more constant, so that nitrogenous oxides existed in th is reactor was removed faster. The highest potential denitrification rate (N20 production) was observed in sludge of reactor . However, N2 gas recovery from nitrate and nitrite transformed by sludge of reactor M was the highest. Linear correlation between nitrogenous oxide reduction with gas production was observed in reactor A, M and P, but not in reactor G. Â